2017
DOI: 10.1177/1049732316688882
|View full text |Cite
|
Sign up to set email alerts
|

Intentional Nonadherence as a Means to Exert Control

Abstract: Medication adherence is a major issue for patients with a chronic illness, who sometimes rationally choose temporary nonadherence. This study aims at better understanding intentional nonadherence and especially why it seems to fluctuate over time. It is based on 48 semi-structured interviews conducted in a hospital in the Netherlands with patients who had been prescribed a medication for a chronic disease for at least 1 year, and who had either type 2 diabetes, hypertension, Parkinson's disease, inflammatory b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…However, a relevant proportion of patients do not stop taking medications because they feel worse but because they feel better. Given the plethora of reasons for intentional nonadherence, an individual approach is necessary to positively modulate adherence in elderly people with PD (31,32). Because many people discontinue medication because of side effects, comprehensive education on side effects and what to do in case of side effects is recommended for every patient.…”
Section: Self-reported Reasons For Nonadherencementioning
confidence: 99%
See 1 more Smart Citation
“…However, a relevant proportion of patients do not stop taking medications because they feel worse but because they feel better. Given the plethora of reasons for intentional nonadherence, an individual approach is necessary to positively modulate adherence in elderly people with PD (31,32). Because many people discontinue medication because of side effects, comprehensive education on side effects and what to do in case of side effects is recommended for every patient.…”
Section: Self-reported Reasons For Nonadherencementioning
confidence: 99%
“…We also found that patients with motor complications (higher MDS-UPDRS IV), which frequently occur in advanced disease stages, tended to demonstrate intentional nonadherence by modifying their prescribed medication. This was probably the result of patients' desire to exert control over the treatment and its effects on their bodies (31). Higher motor problems and the consequent higher total number of drugs per day were associated with less knowledge about the names, reasons, and dosages of their prescribed medication.…”
Section: Factors Associated With Distinct Patterns Of Nonadherencementioning
confidence: 99%
“…Conceptions of patients’ medication use that focus on individual behaviour and patient characteristics have been criticised for having an overly narrow and medically centred orientation (Conrad ), a criticism reiterated in different treatment contexts (Huyard et al . , Lutfey Spencer ). Also, approaches targeting individual medication‐taking behaviour have shown limited effectiveness in terms of improved health outcomes (Nieuwlaat et al .…”
Section: Theorising Patients’ Medication Usementioning
confidence: 99%
“…Patients are framed as active partners in their care, and the emphasis shifts toward facilitating patient choice (including treatment refusal), and reducing blame ( NICE, 2009 ). In practice, however, medication adherence is often indistinct from compliance ( Trnka, 2014 ), and critics have long argued for alternative conceptions of medicine-taking that more accurately account for patient agency, social context, meaning making, and experience ( Britten, 1996 ; Chamberlain et al, 2011 ; Conrad, 1985 ; Dew et al, 2014 ; Donovan & Blake, 1992 ; Drabble et al, 2019 ; Huyard et al, 2017 , 2019 ; Lumme-Sandt et al, 2000 ; McCoy, 2009 ; Murdoch et al, 2014 ; Polak, 2017 ; Polak & Green, 2020 ; Pound et al, 2005 ; Shoemaker & Ramalho de Oliveira, 2008 ; Webster et al, 2009 ; Werremeyer et al, 2017 ). For example, “medicines resistance” captures the creative, hidden work that patients undertake to minimize, modify, and resist medication intake ( Chamberlain et al, 2011 ; Murdoch et al, 2013 ; Pound et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%